Low rate of human papillomavirus vaccination among schoolgirls in Lebanon: barriers to vaccination with a focus on mothers’ knowledge about available vaccines - Abou El-Ola MJ; Rajab MA; Abdallah DI; Fawaz IA; Awad LS; Tamim HM; Ibrahim AO; Mugharbil AM; Moghnieh RA (Dove Medical Press, 2018)
Maria J Abou El-Ola,1 Mariam A Rajab,2 Dania I Abdallah,3 Ismail A Fawaz,4 Lyn S Awad,5 Hani M Tamim,6 Ahmad O Ibrahim,7 Anas M Mugharbil,7 Rima A Moghnieh8 1Department of Obstetrics and Gynaecology, Makassed General Hospital, Beirut, Lebanon; 2Department of Pediatrics, Makassed General Hospital, Beirut, Lebanon; 3Department of Pharmacy, Makassed General Hospital, Beirut, Lebanon; 4Department of Internal Medicine, Iklim Health Foundation Hospital, Mazboud, Mount Lebanon, Chouf, Lebanon; 5Department of Pharmacy, Makassed General Hospital, Beirut, Lebanon; 6Department of Internal Medicine, American University of Beirut, Beirut, Lebanon; 7Division of Hematology/Oncology, Department of Internal Medicine, Makassed General Hospital, Beirut, Lebanon; 8Division of Infectious Diseases, Department of Internal Medicine, Makassed General Hospital, Beirut, Lebanon Background: Human papillomavirus (HPV) infection is an established predisposing factor of cervical cancer. In this study, we assessed the awareness about genital warts, cervical cancer, and HPV vaccine among mothers having girls who are at the age of primary HPV vaccination attending a group of schools in Lebanon. We also assessed the rate of HPV vaccination among these girls and the barriers to vaccination in this community. Subjects and methods: This is a cross-sectional, school-based survey. A 23-item, self-administered, anonymous, pretested, structured questionnaire with closed-ended questions was used to obtain data. The questionnaire was sent to the mothers through their student girls, and they were asked to return it within a week. Data were analyzed using the Statistical Package for Social Sciences version 21.0. Bivariate analysis was performed using the chi-square test to compare categorical variables, whereas continuous variables were compared using the Student’s t-test. Fisher’s exact test was used when chi-square test could not be employed. Results: The response rate in our survey was 39.4%. Among the responders, the rate of awareness about HPV infection was 34%, where 72% of the mothers had heard about cervical cancer, and 34% knew that a vaccine is available to prevent cervical cancer. HPV vaccination uptake rate was 2.5%. This lack of vaccination was primarily attributed to the low rate of mothers’ awareness about the vaccine (34%). Factors significantly affecting awareness about the vaccine were the mothers’ marital age, nationality, level of education, employment, and family income. Barriers to HPV vaccination, other than awareness, were uncertainty about safety or efficacy of the vaccine, conservative ideas of mothers regarding their girls’ future sexual life, and relatively high price of the vaccine. Conclusion: Vaccine uptake is low among eligible girls attending this group of schools. The barriers to vaccination are multiple; the most important one is the mothers’ lack of knowledge about HPV, cervical cancer, and the modes of prevention. Awareness campaigns along with a multimodal strategy that targets the identified barriers would be recommended to achieve higher rates of HPV vaccination. Keywords: awareness, barriers, cervical cancer, human papillomavirus, knowledge, Lebanon, mothers, schools, vaccine